Fruit and Vegetable Intake of Females Before, During, and After Introduction of 3 Bundled Food System Interventions in Urban Vietnam and Nigeria - Pastori, Giulia; Brouwer, Inge D.; Siemonsma, Meike; Verhoef, Hans; Huong, Le Thi; Xuan, Thi Thanh Le; Mai, Truong Tuyet; Samuel, Folake O.; Shittu, Oluyemisi F.; Eyinla, Toluwalope E.; Even, Brice; Hernandez, Ricardo; et al. (Elsevier, 2024)
Background Low fruit and vegetable (FV) intake in low- and middle-income countries, which is associated with noncommunicable diseases and micronutrient deficiencies, requires food system interventions addressing FV accessibility, affordability, and acceptability. Periodic FV intake monitoring during interventions informs progress toward achieving increased intakes and contributes to understanding the effectiveness of these interventions.